Analysis of Jalawure (Tacca leontopetaloides) As a Superior Non-wood Forest Product in Garut Regency - Ary Widiyanto; Aji Winara (Balai Litbang Teknologi Agroforestry, Ciamis, 2021)
ABSTRACTPolynesian arrowroot or Jalawure (Tacca leontopentaloides) are food-producing tubers that grow naturally in coastal areas in several parts of Indonesia. Jalawure is spread on the coast of South Garut, Karimunjawa Islands (Jepara), Bangka Regency and East Belitung Regency. Jalawure was designated as a national puspa on the day of “cinta puspa dan satwa nasional 2014”. This study aimed to analyze the potential of Jawalure as a leading Non-Wood Forest Product (NWFP) in Garut Regency. The analysis was carried out using five criterias listed in the Minister of Forestry Regulation No. 21 Year 2009. The results of the analysis show that jalawure is included in the category of non-seeded NWFPs, with indications of (a) limited demand for jalawure tubers and flour, (b) the absence of a business entity that invests in Jalawure development, (c) the unavailability of policies that encourage Jalawure development and (d) the limited number of farmers who cultivate Jalawure. Therefore, jalawure is not included in the category of NWFPs that have priority for development. Keywords: Food security, NWFP, Polynesian arrowroot, Superior